Developing strategic syura tool to enhance effectiveness of meeting - Abdul Wahab, Muhammad Nubli; Kassim, Hafizoah (2007)
Meeting is the most important tool in managing organization. However, study shows that meeting is not conducted effectively. Many problems occur during the process. These problems lead to the deficiency of organizational decision making and its performance (Gregorian, 2006). This research is very important in providing meeting too is to improve the performance of the meeting. Study shows that due to ineffective conduct of meetings, many problems occur that lead to the deficiency of organizational decision making and performance (Gregorian, 2006). This study is important to provide employers with a measuring tool to identify the weaknesses when conducting meeting. It covers six different domains of a meeting which include chairperson's perspective, participants' perspective, process perspective, minutes, contents and implementation of the meeting. After capturing the performance of the meeting, this research provides a special tool to tie up the problems of meeting with the proper solution. As a result, the user can improve their meeting skills by identifying the correct way of conducting meeting. This research produced ready-touse meeting kit to improve performance of meeting. The kit includes: software on measuring effectiveness of meeting, syura descriptors and syura notes. The uses of the kit will help improve decision making process of the organization through meeting as well as improving the organizational performance.